Nanoporous silica glass sensibilisation in respect to the gas components detection - Novikov, Alexander F. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Techniques and technology for a specific surface treatment of the nanoporous (~8 nm) silicate glass is presented and discussed. That treatment is aimed at the achievement of the sample sensitivity to individual chemical components of atmosphere and other gas mixtures. The treatment technology is based on the impregnation of the nanoporous glass plates with solutions of different pH and other colour indicators and dyes. After the solvent evaporation, the indicator molecules remain immobilized in the pores of glass. The immobilized molecules are able of active interaction with ambient gas molecules. Those interactions are specific and they reveal themselves in the samples spectral changes (in visible and infrared wave range), including spectral absorbance and fluorescence. So, it has turned out that a selective detection of the gas mixture components and estimation of its concentration are possible. Physical and chemical interpretations of the observed phenomena are presented.
Optica Applicata, Vol. 38, 2008, nr 1, s. 65-74
Keywords: optyka; silicate porous glasses; glass surface properties; optical gas sensors; interface molecular interactions; chemical hard and soft acids and bases